New chromadorid nematodes from Brazilian coral reefs: a taxonomic contribution to Chromadora Bastian, 1865 - Neres, Patrícia Fernandes; Dos Santos, Paulo Jorge Parreira; Esteves, André Morgado (Zootaxa, 2021)
A study involving experiments on a natural Brazilian coral reef, with the aim of assessing the impacts that may be caused by an increase in sea level on benthic fauna, showed that Chromadoridae Filipjev, 1917 was the most abundant and diverse family of Nematoda. Our results also showed that Chromadora Bastian, 1865 was the most abundant and diverse genus, represented by three species: C. serrambi sp. nov., C. pernambucana sp. nov. and C. macrolaimoides Steiner, 1915. Chromadora serrambi sp. nov. is the only Chromadora species where pre-cloacal supplements are absent. Chromadora pernambucana sp. nov. is differentiated by gubernaculum shape and by three supplements, of which two are cup-shaped (small and slightly sclerotized) and a pre-cloacal papilla very close to the cloaca. Chromadora macrolaimoides is very similar to specimens described previously. Here, we propose a grouping of species based on features considered to be most relevant for species identification and present it as an illustrated guide. The diagnostic characteristics of all species were considered, and following discussions, C. micropapillata was revalidated. Finally, the most relevant diagnostic characteristics for the differentiation of Chromadora species were highlighted.